A Rock Fracturing Method Using High-Pressure Gas Expansion: Case Study on Its Application in Hangzhou-Lin’an Intercity Railway - Dunwen Liu; Yu Tang; Caiwu Cai; Yinghua Jian (Advances in Civil Engineering)
The use of explosives in cities is under strict control due to the risks associated with blasting. It is difficult to perform nonexplosive continuous excavation on hard rock connecting passage in crowded cities with dense high buildings and populations safely and rapidly. Therefore, a new method of rock fracturing through high-pressure gas expansion is proposed. The method was applied for the excavation of a connecting passage on the Hangzhou-Lin’an Intercity Railway in China. Analysis was conducted on the parameters of rock fracturing, rock fracturing effects of this method, and its impact on the vibration of surrounding buildings. Overall, when the compressive strength of rock reaches 100 MPa, and the surrounding rocks are dense, this method of rock fracturing can fully meet the requirements of rapid excavation in a connecting passage, and the vibration resulting from rock fracturing causes only a slight disturbance to the adjacent buildings. After optimizing the rock fracturing parameters, better, smoother rock fracturing effects are obtained, and a set of safe and efficient solutions to the excavation of hard rock in cities are created. It can provide a new approach for rock fracturing in similar projects.